Methods and devices for mapping data files - Clifton-Bligh, Gervase (2004)
A method of mapping interconnections between a plurality of data files, such as files of the world wide web. The method comprises a step of, for a first file, in a display area displaying a first region. Then, according to a first distance scale, displaying one or more second regions, which respectively represent one or more second files logically related to the first file, for example by hyperlinks. The second regions are spatially related in a display to the first region. In (n-1) further steps, i=2,... , n, the method displays according to an i-th distance scale smaller than the (i-1)-th distance scale one or more (i+1)-th regions. Each of these (i+1)-th regions respectively represent one or more (i+1)-th files which are logically related to the i-th file, and they are spatially related on a display to the i-th region representing that i-th file. The method may be implemented in software, for example in a web browser.